2013
DOI: 10.1111/jfs.12091
|View full text |Cite
|
Sign up to set email alerts
|

Use of Novel Lactic Acid Bacterial Strains with Antagonistic Activity for the Preparation of Safe Indigenous Fermented Dairy Foods (Dahi and Raita)

Abstract: Attempts were made to isolate natural antagonistic lactic acid bacteria (LAB) and use them in production of dahi and raita for increased safety. Seventy isolates of LAB were isolated from dahi obtained from different sources. These isolates were tested for their antagonistic activity against selected pathogenic strains of Staphylococcus aureus subsp. aureus and Escherichia coli AB 1157 by adopting agar well assay method. Out of the 70 lactic acid bacterial isolates, 8 were found to have antagonistic activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…For probiotics, the possible mechanisms for the reduction in pathogens are competition for nutrients and sites of adhesion in the mucosa of the small intestine (LutfulKabir, 2009), stimulation of adaptive immunity and alteration of the caecal microbiome (Neal-McKinney et al, 2012). Furthermore, the inhibitory effects on the growth of several enteropathogenic bacteria are likely associated with the antimicrobial compounds produced by LAB, such as bacteriocin and lactic, acetic and other short-chain organic acids, which are responsible for a reduction in the intestinal pH (Cheng, Yu, & Chou, 2003;LutfulKabir, 2009;Servin & Coconier, 2003;Varalakshmi, Balasubramanyam, Surendranath, Bagath, & Rajendran, 2013). These indicate the synergistic effects of organic acids and probiotics in improving the intestinal health of poultry.…”
Section: Discussionmentioning
confidence: 99%
“…For probiotics, the possible mechanisms for the reduction in pathogens are competition for nutrients and sites of adhesion in the mucosa of the small intestine (LutfulKabir, 2009), stimulation of adaptive immunity and alteration of the caecal microbiome (Neal-McKinney et al, 2012). Furthermore, the inhibitory effects on the growth of several enteropathogenic bacteria are likely associated with the antimicrobial compounds produced by LAB, such as bacteriocin and lactic, acetic and other short-chain organic acids, which are responsible for a reduction in the intestinal pH (Cheng, Yu, & Chou, 2003;LutfulKabir, 2009;Servin & Coconier, 2003;Varalakshmi, Balasubramanyam, Surendranath, Bagath, & Rajendran, 2013). These indicate the synergistic effects of organic acids and probiotics in improving the intestinal health of poultry.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al (2003) studied the influence of organic acids, including acetic acid, propionic acid and lactic acid on the growth and survival of E. coli O157:H7. The authors reported that lactic acid exerts greater inhibitory effects on the growth of the pathogenic bacteria than acetic acid and propionic acid; however, the combination of the organic acids exhibited an important synergic effect in the inhibition of this pathogen (Cheng et al 2003, Varalakshmi et al 2013). According to Diez-Gonzalez & Russell (1997) small amounts of sodium acetate (1.6g.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the inhibitory effect on the growth of several enteropathogenic bacteria is likely associated with the antimicrobial compounds produced by lactic acid bacteria, such as bacteriocin and lactic, acetic and other short-chain organic acids, which are responsible for a reduction in the intestinal pH (Servin & Coconnier 2003, Cheng et al 2003, Varalakshmi et al 2013. Lactic acid represents the main antimicrobial compound present in cultures of lactic acid bacteria (Earnshaw 1992, Navarro et al 2000, Todorov & Dicks 2005, Rossland et al 2005, Moraes et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…; Varalakshmi et al . ). Although central China has only a poor tradition of dairy consumption, nomadic groups living in Inner Mongolia, the Tibetan Plateau and Xinjiang Tianshan and Altai Mountain regions have developed a variety of distinctive traditional local fermented dairy products, such as koumiss, cheese, irimshik, kefir and sour cream from fermented sheep, mare, camel and yak milk (Irigoyen et al .…”
Section: Introductionmentioning
confidence: 97%
“…The lactic acid bacteria (LAB) microflora in traditional fermented dairy foods plays an important role in conferring the dairy products' specific characteristics and indigenous flavour (Leroy and Vuyst 2004;Yu et al 2011;Varalakshmi et al 2014). Although central China has only a poor tradition of dairy consumption, nomadic groups living in Inner Mongolia, the Tibetan Plateau and Xinjiang Tianshan and Altai Mountain regions have developed a variety of distinctive traditional local fermented dairy products, such as koumiss, cheese, irimshik, kefir and sour cream from fermented sheep, mare, camel and yak milk (Irigoyen et al 2005;Yi et al 2011;Ao et al 2012;Zuo et al 2013).…”
Section: Introductionmentioning
confidence: 99%